Synthesis method and application of polyacrylonitrile-based pressureless quick filtration phosphorus removal fiber material
Patent Information
- Application Number
- CN202311560100.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-21
AI Technical Summary
[0006]针对目前对外源性含磷废水的治理方法存在处理效率低,耗能较高等问题,本发明提供了一种PAN基纳米铁材料、制备方法及应用,该方法以热诱导相分离法合成了可定制的具有微孔结构的PAN载体,利用有机改性方法对其进行胺化接枝,从而实现铁的载荷
[0022](1)本材料利用无模板式热诱导性分离法合成聚丙烯腈基底材料,材料合成方便,尺寸可定制化,胺化改性后对于金属离子具有螯合能力,因而表现出对Fe3+的高吸附量,可根据母液铁离子浓度的调节和材料基底的尺寸大小进而控制铁的负载量,材料的载铁量可控制在1%-5%之间。
Smart Images

Figure CN117816130B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental functional materials, and more specifically, relates to the preparation method and application of iron-loaded amination thermally induced phase separation organic materials. Background Technology
[0002] Reducing exogenous phosphorus input has become an important means of curbing eutrophication in lakes and reservoirs. Exogenous phosphorus control technologies include coagulation and sedimentation, adsorption, biological treatment, and membrane treatment. Among these, adsorption has received widespread attention due to its simple operation, low cost, and high selectivity, which has also led to continuous research on phosphate adsorbents. Iron is a metallic element widely found in nature, and its strong specific adsorption of phosphate has made it a subject of extensive research in the field of phosphorus removal. The article "Development of polymer-based nanosized hydrated ferric oxides (HFOs) for enhanced phosphate removal from waste effluents" in Volume 43 of *Water Research* in 2009 introduces HFO-201, a phosphate adsorbent material obtained by combining a strongly basic anion exchange resin with iron. Since its development, HFO-201 has been successfully commercialized and used in the adsorption stage of fixed columns for advanced phosphorus removal in wastewater treatment plants, achieving good results.
[0003] HFO-201 is a uniformly sized small-particle iron-loaded resin. CN 200510095177.5 describes its main synthesis method: a FeCl3, HCl, and NaCl solution with a concentration ratio of 1:20:10 is prepared and passed through a strongly basic anionic D-201 resin placed in an adsorption column at a flow rate of 2-5 BV / h; the above Fe... 3+ The permeated D-201 resin is centrifuged and dehydrated. Then, the centrifuged and dehydrated D-201 resin is rapidly added to a mixed solution of NaOH and NaCl at a mass ratio of 8% and 3% respectively, and reacted at 40-80℃ for 12-24 hours to obtain a resin-based phosphorus removal adsorbent. This product contains approximately 10% iron and has a phosphorus removal capacity of approximately 20 mg P / g. Because it fully utilizes the synergistic advantages of iron and resin in phosphorus recovery, and its synthesis principle and operation are relatively simple and easy to industrialize, it is widely used as a fixed column adsorption packing. However, due to carrier limitations, it cannot be used as a good filter media for pressureless filter beds. These problems are mostly caused by surface mass transfer of the resin material and the diffusion process of pollutant particles. HFO-201 particles have a size of approximately 1 mm, an average pore size of 20.3 nm, and a density of approximately 0.786 g / cm³. 3 Its small size and aperture make it difficult to handle large volumes of water flowing by gravity without external pressure.
[0004] Polyacrylonitrile (PAC) is an inexpensive and common polymer chemical with stable chemical properties and high resistance to inorganic acids, bleaching powder, hydrogen peroxide, and common organic reagents. The nitrile groups abundant on the surface of PAC can generate carboxylic acids through hydrolysis and amines through reduction, thus attracting extensive research. Among them, the paper "Fabrication of mesoporous polymer monolith: a template-free approach" published in Volume 47 of *Chemical Communications* in 2011 introduces a template-free method for preparing PAC bulk materials using thermally induced phase separation technology. This material has a high specific surface area and is rich in mesoporous and macroporous structures, providing more active adsorption centers and interconnected macroporous structures for ion diffusion.
[0005] The ability to chelate and adsorb metal ions through amination modification is also a major characteristic of polyacrylonitrile (PAN). For example, the paper "Swollen-layer constructed with polyamine on the surface of nano-polyacrylonitrile cloth used for extract uranium from seawater," published in *Chemosphere*, Volume 271, 2021, introduces a surface-swellable electrospun fabric for adsorbing and recovering hexavalent uranium from seawater using polyethyleneimine-grafted modified PAN. The modified PAN surface is rich in amino and imine groups, which can bind a large number of uranium ions. The material achieved an adsorption capacity of 215.25 mg U / g in adsorption experiments and 144.5 mg U / g in simulated seawater. Based on this theory, we hope to develop a pressureless filter bed media with adjustable size, large pore size, and high water throughput by using PAN block material as a carrier and amination for iron ion adsorption. Summary of the Invention
[0006] To address the problems of low treatment efficiency and high energy consumption in current methods for treating exogenous phosphorus-containing wastewater, this invention provides a PAN-based iron nanomaterial, its preparation method, and its application. This method synthesizes a customizable PAN carrier with a microporous structure using a thermally induced phase separation method, and then performs amination grafting using an organic modification method to achieve iron loading. When the material is added to water, the Fe on its surface and in its pores... 3+ FeO(OH) can rapidly and specifically bind with phosphate ions in water to form stable FePO4 crystals. The amine groups on its surface also protonate at low pH levels, allowing for electrostatic adsorption and binding of phosphate ions, thus exhibiting highly efficient phosphorus removal capabilities. To address the above problems, the technical solution adopted in this invention is as follows:
[0007] A method for preparing an organic adsorbent, comprising the following steps:
[0008] 1) Prepare a precursor solution of polyacrylonitrile, distilled water and organic solvent for thermally induced phase separation;
[0009] 2) React the precursor liquid system until homogeneous under heating and stirring conditions;
[0010] 3) Allow the liquid obtained in step 2) to stand at room temperature for a cooling phase separation process;
[0011] 4) The product obtained in step 3) is washed with alcohol and dried to obtain the iron-supported PAN-monolith;
[0012] 5) At a certain temperature, PAN-monolith is reacted in a certain concentration of diethylenetriamine, followed by washing and drying;
[0013] 6) Add the product obtained in step 5) to an aqueous solution of iron salt of a certain concentration and stir to react;
[0014] 7) Filter out the product obtained in step 6), wash with distilled water, and freeze dry to obtain iron-loaded polyacrylonitrile filter material; the organic solvent in step 1) is dimethyl sulfoxide; the volume ratio of distilled water to organic solvent is between 1:8 and 1:10; the mass ratio of polyacrylonitrile powder to liquid phase is between 1:9 and 1:12.
[0015] Preferably, the reaction temperature in step 2) is 60℃-95℃, and the room temperature in step 3) is 20℃-30℃. This synthesis method is template-free, and the container used in the phase separation stage determines the properties and size of the finished material.
[0016] Preferably, the alcohol in step 4) is methanol or ethanol.
[0017] Preferably, the concentration of diethylenetriamine in step 5) is 50%-100% by volume, the water bath temperature in step 5) is 80℃-120℃, and the reaction time is 3-5h.
[0018] Preferably, the washing solution in step 5) is a 0.4-1M HCl and NaOH solution.
[0019] Preferably, the iron salt in step 6) is FeCl3 or Fe(NO3)3, the concentration of iron ions in the aqueous solution of the iron salt is 0.05-0.4 mol / L, the solid-liquid ratio of the stirring reaction in step 6) is 1:10-1:250, and the stirring time is 12-24 h.
[0020] The present invention also provides an iron-loaded polyacrylonitrile filter material (Fe-NH2-PAN) obtained by the above preparation method. The Fe-NH2-PAN is in the form of brown lumps. The particle size of the Fe-NH2-PAN material can be customized to 0.4-5 cm according to requirements. The iron loading in the Fe-NH2-PAN material is 1%-5%.
[0021] Beneficial effects:
[0022] (1) This material utilizes a template-free thermally induced separation method to synthesize a polyacrylonitrile substrate. The material is easy to synthesize, its size can be customized, and after amination modification, it exhibits chelating ability for metal ions, thus demonstrating Fe... 3+ The high adsorption capacity allows for control of the iron loading by adjusting the iron ion concentration in the mother liquor and the size of the material substrate. The iron loading of the material can be controlled between 1% and 5%.
[0023] (2) After amination modification, the primary amines on the surface of this material will protonate under acidic conditions and exhibit a positively charged state, thus possessing electrostatic attraction for phosphate groups. The Fe in its surface and pores... 3+ FeO(OH) can quickly and specifically bind with phosphate in water to form stable FePO4 crystals. The amine groups on the surface will also be protonated at low pH and adsorb phosphate by electrostatic force, thus having a highly efficient phosphorus removal capacity.
[0024] (3) Currently, the main method for deep treatment of phosphorus-containing wastewater is fixed column adsorption, which relies on external pressure to achieve a certain water flow efficiency. In contrast, this material is rich in mesopores and macropores, and the size can be customized. It is not only suitable for fixed column adsorption, but can also achieve high water flow and treatment effect under pressureless conditions. Attached Figure Description
[0025] Figure 1 Flowchart of material synthesis
[0026] Figure 2a SEM image (front view) of the material surface
[0027] Figure 2b SEM image of the material surface (side view)
[0028] Figure 3 Material XRD images
[0029] Figure 4a Schematic diagram of the competitive adsorption performance of the material Fe-PAN-NH2-1
[0030] Figure 4b Schematic diagram of the competitive adsorption performance of Fe-PAN-NH2-2 material
[0031] Figure 5 Schematic diagram of material adsorption kinetics
[0032] Figure 6 Schematic diagram of material column experimental performance Detailed Implementation
[0033] Example 1:
[0034] 1) Prepare 10 ml of a DMSO-water mixture with a volume ratio of 9:1, add 1.2 wt% polyacrylonitrile powder, and dissolve by stirring in a sealed container at 75°C.
[0035] 2) Cool the product obtained in step 1) at room temperature until it solidifies, and then demold it;
[0036] 3) The product obtained in step 2) was placed in a methanol solution, stirred and washed for 6 hours, and then freeze-dried.
[0037] 4) The product obtained in step 3) was placed in a diethylenetriamine solution with a volume ratio of 80 vol% and stirred at 95°C for 3 h for amination. The solid-liquid ratio of the reaction was 1:65.
[0038] 5) The product obtained in step 4) is washed and freeze-dried to obtain product PAN-NH2;
[0039] 6) Add 0.021 mol Fe·L to the above PAN-NH2 block material. -1 (0.1mol·L -1 The reaction was carried out in an aqueous solution of FeCl3·H2O for 12 hours with stirring, and the solid-liquid ratio was 1:65.
[0040] 7) Filter out the reactants from step 6), wash with pure water until neutral, and freeze-dry to obtain iron-supported polyacrylonitrile filter media (named Fe-PAN-NH2-1).
[0041] The material prepared in this example is brown and blocky. The carrier PAN-NH2 has a porous structure with a pore size of 2-4 μm, as shown in Figure 2. The iron nanoparticles have a particle size of approximately 5-10 nm, and their loading after digestion, measured by ICP, is approximately 2.43%, indicating successful iron loading. Iron is distributed in the form of nanoparticles on the surface of the material carrier, such as... Figure 2b As shown; XRD analysis was performed on the sample, and the results are as follows. Figure 3 As shown, the material carrier, as an organic phase, does not exhibit obvious characteristic peaks. In the XRD pattern, iron exists in the form of FeO(OH). Mercury porosimetry analysis reveals that the material has a porosity of 47.4%, with large pores having an average pore size of approximately 688.54 nm. This high porosity and large pore size are beneficial for water permeability and for the handling of PO4. 3- Adsorption.
[0042] Example 2:
[0043] 1) Prepare 10 ml of a DMSO-water mixture with a volume ratio of 9:1, add 1.2 wt% polyacrylonitrile powder, and dissolve by stirring in a sealed container at 75°C.
[0044] 2) Cool the product obtained in step 1) at room temperature until it solidifies, and then demold it;
[0045] 3) The product obtained in step 2) was placed in a methanol solution, stirred and washed for 6 hours, and then freeze-dried.
[0046] 4) The product obtained in step 3) was placed in a diethylenetriamine solution with a volume ratio of 80 vol% and stirred at 95°C for 3 h for amination. The solid-liquid ratio of the reaction was 1:65.
[0047] 5) The product obtained in step 4) is washed and freeze-dried to obtain product PAN-NH2;
[0048] 6) Add 0.021 mol Fe·L to the above PAN-NH2 block material. -1 (0.1mol·L -1 The reaction was carried out in an aqueous solution of FeCl3·H2O for 12 hours with stirring, and the solid-liquid ratio was 1:65.
[0049] 7) Adjust the pH of the system in step 6) to 12.0 and continue stirring for 12 hours. Filter out the precipitated reactants in step 6), wash with pure water until neutral, and freeze-dry to obtain iron-supported polyacrylonitrile filter media (named Fe-PAN-NH2-2).
[0050] The material prepared in this example is brown and blocky. The carrier PAN-NH2 has a porous structure with a pore size of 2-4 μm, as shown in Figure 2. The iron nanoparticles have a particle size of approximately 5-10 nm, and their loading after digestion, measured by ICP, is approximately 2.82%, indicating successful iron loading. Iron is distributed in the form of nanoparticles on the surface of the material carrier, such as... Figure 2b As shown; XRD analysis was performed on the sample, and the results are as follows. Figure 3 As shown, the material carrier, as an organic phase, does not exhibit obvious characteristic peaks. In the XRD pattern, iron exists in the form of FeO(OH). Mercury porosimetry analysis reveals that the material has a porosity of 74.11%, with large pores having an average pore size of approximately 200.81 nm. This high porosity and large pore size are beneficial for water permeability and for the transport of PO4. 3- Adsorption.
[0051] Application Example 1
[0052] Example of testing the static adsorption effect of Fe-PAN-NH2-2 on phosphate in water under the presence of competing ions: Preparation containing PO42- 3- Cl- NO3 - SO4 2- HCO3 - SiO3 2- The mixture was controlled to have a concentration of 50 mg P·L. -1 The concentration of competing anions was controlled at 60 mg·L⁻¹. -1 300mg·L -1 and 1200 mg·L -1 The initial pH was 7.0, and the material dosage was 0.5 g·L⁻¹. -1 The mixture was stirred and adsorbed at room temperature for 24 hours. The supernatant was then collected to measure PO4. 3- concentration.
[0053] like Figure 4b As shown, Cl - NO3 - and HCO3 - The effect on the adsorption effect of Fe-PAN-NH2-2 is relatively small at 300 mg·L⁻¹. -1 Under competitive anion conditions, its adsorption capacities were 79.46%, 91.13%, and 61.83% of the control group, respectively, while SO42-... 2- and SiO3 2- Its stronger electrostatic adsorption shielding effect has a significant impact on the material's adsorption performance. The above results indicate that the material still exhibits strong adsorption performance in the presence of competing anions.
[0054] Under the same initial conditions, Fe-PAN-NH2-1 material has a relatively high adsorption capacity, but it is difficult to guarantee a high phosphorus removal effect in adsorption environments with high concentrations of competing ions.
[0055] Application Example 2
[0056] Static phosphate adsorption kinetics experiments were conducted on materials Fe-PAN-NH2-1 and Fe-PAN-NH2-2 to determine the rate of phosphate binding: a solution containing 50 mg P·L -1 The solution was used as the target water body for treatment. The initial pH was 7.0, and the material dosage was 0.5 g·L⁻¹. -1 The mixture was stirred and adsorbed at room temperature for 24 hours. The supernatant was collected at different time intervals to measure PO4. 3- concentration.
[0057] like Figure 5 As shown, Fe-PAN-NH2-1 does not undergo precipitation, so the iron in the material exists in a weakly crystalline state and a small amount of free state. When the material is added to water, some of the iron will hydrolyze to generate a large number of positive charges, which can bind to phosphates in the water at a relatively fast rate, thus exhibiting fast adsorption kinetics.
[0058] Under the same initial conditions, after precipitation, the iron in Fe-PAN-NH2-2 exists in the form of FeO(OH). When the material is added to water, the iron combines with the phosphate in the water more slowly, resulting in slower kinetics.
[0059] Application Example 3
[0060] Pressureless column adsorption was performed on Fe-PAN-NH2-2 material to determine its performance under practical application conditions. The filter column was unsealed, and the flow rate was controlled by adjusting the liquid level in the adsorbent. The adsorbent flowed entirely by gravity. A solution containing 1 mg P·L was prepared. -1 The solution was used as the target water body for treatment, containing 30 mg of SO4. 2- ·L -1 As a competing ion, 20 ml of wet material was used for adsorption, and the water flux was controlled at 1.715 L·h. -1 (86BV·h -1 The adsorption process is carried out. Samples are taken at different time intervals to measure the PO4 in the effluent. 3- concentration.
[0061] like Figure 6 As shown, at approximately 86 BV·h -1 At a flow rate of [value missing], the material can reduce the phosphorus concentration in the influent to approximately 0.75 mg P·L. -1 It has high application potential.
Claims
1. The application of an iron-loaded polyacrylonitrile filter media in a pressureless filter bed for treating phosphorus-containing water, characterized in that: The preparation method of the iron-loaded polyacrylonitrile filter material includes the following steps: 1) preparing a precursor liquid of polyacrylonitrile powder, distilled water and organic solvent for thermally induced phase separation; 2) reacting the precursor liquid system until homogeneous under heating and stirring conditions; 3) allowing the liquid obtained in step 2) to stand at room temperature for cooling phase separation; 4) washing and drying the product obtained in step 3) to obtain the iron-loaded material. 5) At a certain temperature, the iron-supported material is reacted in a certain concentration of diethylenetriamine, followed by washing and drying; 6) The product obtained in step 5) is added to an aqueous solution of iron salt of a certain concentration and stirred to react; 7) The product obtained in step 6) is filtered out, washed with distilled water, and freeze-dried to obtain the iron-supported polyacrylonitrile filter material Fe-NH2-PAN; the organic solvent in step 1) is dimethyl sulfoxide; the volume ratio of distilled water to organic solvent is 1:8-1:10; the mass ratio of polyacrylonitrile powder to liquid phase is 1:9-1:12; the reaction temperature in step 2) is... The temperature range is 60℃-95℃, and the room temperature in step 3) is 20℃-30℃; the iron salt in step 6) is FeCl3 or Fe(NO3)3, and the concentration of iron ions in the aqueous solution of the iron salt is 0.05-0.4mol / L; the solid-liquid ratio of the stirring reaction in step 6) is 1:10-1:65, and the stirring time is 12-24h; the iron-loaded polyacrylonitrile filter material Fe-NH2-PAN is brown and lumpy, the particle size of the Fe-NH2-PAN material is 0.4-5cm, and the iron loading in the Fe-NH2-PAN material is 1%-5%.
2. The application according to claim 1, characterized in that: The alcohol mentioned in step 4) is methanol or ethanol.
3. The application according to claim 1, characterized in that: The reaction temperature in step 5) is 80℃-120℃, and the reaction time is 3-5h.
Citation Information
Patent Citations
Prepn process of resin-based dearsenifying adsorbent
CN1772370A
Iron ion immobilized aminated acrylic fiber as well as preparation method and application thereof
CN115198535A